2020
DOI: 10.1186/s13071-020-04342-5
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles metabolic proteins in malaria transmission, prevention and control: a review

Abstract: The increasing resistance to currently available insecticides in the malaria vector, Anopheles mosquitoes, hampers their use as an effective vector control strategy for the prevention of malaria transmission. Therefore, there is need for new insecticides and/or alternative vector control strategies, the development of which relies on the identification of possible targets in Anopheles. Some known and promising targets for the prevention or control of malaria transmission exist among Anopheles metabolic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 270 publications
(459 reference statements)
1
28
0
Order By: Relevance
“…gambiae to halofenozide and 20E both decrease P. berghei oocyst prevalence and intensity, the authors of these studies observed that only 20E induced the expression of immune genes [24,106], therefore leaving unanswered the question of what could be the potential non-immune mechanisms by which 20E agonists regulate P. berghei competence. Possibilities include that DBH compounds regulate epigenetic modifications [165,166], the formation of the peritrophic matrix [167], the expression of specific midgut factors that are essential for Plasmodium invasion [112], metabolism [142], signaling pathways (e.g. c-Jun N-terminal kinase [JNK] pathway), or all of these simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae to halofenozide and 20E both decrease P. berghei oocyst prevalence and intensity, the authors of these studies observed that only 20E induced the expression of immune genes [24,106], therefore leaving unanswered the question of what could be the potential non-immune mechanisms by which 20E agonists regulate P. berghei competence. Possibilities include that DBH compounds regulate epigenetic modifications [165,166], the formation of the peritrophic matrix [167], the expression of specific midgut factors that are essential for Plasmodium invasion [112], metabolism [142], signaling pathways (e.g. c-Jun N-terminal kinase [JNK] pathway), or all of these simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…As with classic insecticides, the first [185] Daphnia magna [186] mechanism involves an increase in the activity of detoxification enzymes such as carboxylesterase, aryl-acylamidase, cytochrome P450s or glutathione-S-transferases [138][139][140][141]. While an increased expression of cytochrome P450s also constitutes the resistance mechanism of some carbamates, pyrethroids and organochlorines (reviewed in [142]), it is interesting to note that cross-resistance between DBH compounds and these classic insecticides is not always guaranteed (see following paragraph). The second resistance mechanism, identified in P. xylostella, involves the microRNA miR-189942, which decreases the expression of the EcR-B isoform, thereby reducing the susceptibility to fufenozide (because fewer binding sites are available for the 20E agonist) [143].…”
Section: The Potential Of Chemical Control Interventions Targeting 20e Signalingmentioning
confidence: 99%
“…The other two hsp genes found to be overexpressed in the natural populations compared with Ngoussou were hsp90_beta and hsp70 1/8. Trehalose (synthesized by TPS 1/2) contribute to the maintenance of warm temperature, a condition needed for survival of Anopheles [43,70] and is known to promote longevity, fecundity and cold tolerance in insects [46]. TPS 1/2 was also found to be overexpressed in heat-hardened, unexposed, and permethrin-resistant females, compared with Ngoussou, with the highest expression in heat-hardened females.…”
Section: Common Metabolic Resistance Genes Are Associated With Thermomentioning
confidence: 98%
“…To investigate the potential role of pleiotropic genes on thermotolerance and insecticide resistance, 3-4 day-old females which survived exposure at 44°C for 30min (and allowed to rest for 12h), those which survived exposure to 0.75% permethrin and unexposed females were used for qRT-PCR, targeting 9 genes previously associated with thermotolerance and/or insecticide resistance [20,31,[43][44][45][46]. These include 6 heat shock proteins: [hsp90 molecular chaperone HtpG (AGAP006959), hsp90 beta (AGAP001424), hsp83 (AGAP006958), hsp70 1/8 (AGAP004944), hsp90 ATPase activator (AGAP010514) and hsp70 (AGAP004581)]; trehalose-6-phosphate synthase/phosphatase (TPS 1/2, AGAP008227), and 2 ionotropic receptor genes, IR21a (AGAP008511) and IR25a (AGAP010272).…”
Section: Transcriptional Profiling Of Thermotolerance-related Genes Umentioning
confidence: 99%
“…In particular, many of these ontologies were associated with metabolic processes, including "cellular metabolic process" (GO:0044237), "catalytic activity" (GO:0003824) and "generation of precursor metabolites and energy" (GO:0006091). Between R-C conditions, additional metabolic ontologies were upregulated, including "generation of precursor metabolites and energy" (GO:0006091) and "cellular metabolic process" (GO:0044237), potentially associated with increased physiological stress in response to insecticide exposure (21). S2.…”
Section: Differentially Expressed Genes Associated With Malathion Resistancementioning
confidence: 99%